Visual therapy through the application of plants and design elements in landscape - I, Krisantia; S, Faris; S, Sazwani (IOP Publishing, 2021)
This paper will explore how visual therapy can help to reduce stress through the use of plants and appropriate design elements. Urban residents in general are experiencing mental stress due to life pressure. With limited usage of the green spaces, the visual landscape has become more significant in how parks can be enjoyed by users while maintaining safe social distancing. One of the functions of using plants in landscape design is as visual therapy to tackle the mental stress problems. Other than plants, applications of basic design elements may help to contribute to the positive properties of the visual landscape. Literature review was used to cover the subject of visual therapy in the landscape. The results have shown that: i-'visual natural element' gives a positive impression of the soul and creates a feeling of calmness, ii-visual characteristics of the plant such as form, colour and texture contributed to the effect of therapy in the landscape. The results from this study may help to highlight the importance of landscape as a form of visual therapy after Covid-19 and the highlighted characteristics of the plants and design elements may present opportunities for landscape architects to help build more usable green spaces and cities.